Angelica gigas Nakai and Soluplus-Based Solid Formulations Prepared by Hot-Melting Extrusion: Oral Absorption Enhancing and Memory Ameliorating Effects. - Jingpei Piao; Jae-Young Lee; Jin Bae Weon; Choong Je Ma; Hyun-Jeong Ko; Dae-Duk Kim; Wie-Soo Kang; Hyun-Jong Cho (PLoS ONE, 2015)
Oral solid formulations based on Angelica gigas Nakai (AGN) and Soluplus were prepared by the hot-melting extrusion (HME) method. AGN was pulverized into coarse and ultrafine particles, and their particle size and morphology were investigated. Ultrafine AGN particles were used in the HME process with high shear to produce AGN-based formulations. In simulated gastrointestinal fluids (pH 1.2 and pH 6.8) and water, significantly higher amounts of the major active components of AGN, decursin (D) and decursinol angelate (DA), were extracted from the HME-processed AGN/Soluplus (F8) group than the AGN EtOH extract (ext) group (p < 0.05). Based on an in vivo pharmacokinetic study in rats, the relative oral bioavailability of decursinol (DOH), a hepatic metabolite of D and DA, in F8-administered mice was 8.75-fold higher than in AGN EtOH ext-treated group. In scopolamine-induced memory-impaired mice, F8 exhibited a more potent cognitive enhancing effect than AGN EtOH ext in both a Morris water maze test and a passive avoidance test. These findings suggest that HME-processed AGN/Soluplus formulation (F8) could be a promising therapeutic candidate for memory impairment.